The relationship between pain and suicidal vulnerability in adolescence: a systematic review - Hinze, V; Crane, C; Ford, T; Buivydaite, R; Qiu, L; Gjelsvik, B (Elsevier, 2019)
Leading suicide theories and research in adults suggest that pain can exacerbate the suicidal risk of an individual. Although pain and suicidality (including suicidal ideation, behaviour, and death by suicide) both increase in prevalence during adolescence, the relationship between these factors remains unclear. We aimed to systematically review the empirical evidence for such an association in adolescence. We included 25 observational studies published between January 1961 and December 2018, exploring the potential association between pain and suicidality in adolescents aged 10-19 years. Across various samples and manifestations of pain and suicidality, we found that pain approximately doubles the suicidal risk in adolescents, with a few studies suggesting that pain can predict suicidality longitudinally. Although depression was an important factor, it did not fully explain the association between pain and suicidality. Evidence for associations between pain characteristics and suicidality is sparse and inconclusive, and potentially hides developmental differences between adolescents and adults. Identification of psychological mediators and moderators is required to develop interventions tailored to the needs of adolescents experiencing pain. This study is registered with the PROSPERO database, number CRD42018097226.